THE INFLUENCE OF THE CHARACTERISTICS OF THE BOARD OF DIRECTORS AND AUDIT COMMITTEE ON FINANCIAL DISTRESS IN INDUSTRIAL SECTOR COMPANIES ON THE IDX - Maulani, Tisna; Dwiyanjana Santyo Nugroho (Count : Journal of Accounting, Business and Management, 2024)
The influence of the characteristics of the board of directors and audit committee is very important on financial distress. This research aims to determine the effect of the size of the board of directors, independence of the board of directors, knowledge of the board of directors, size of the audit committee, independence of the audit committee and knowledge of the audit committee on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. This research uses a quantitative methodology by applying a basic correlational research approach using secondary data and documentation methods. The population is all industrial sector companies listed on the IDX. The results of this research are that the financial knowledge of the board of directors has a positive effect on financial distress in industrial sector companies listed on the Indonesian Stock Exchange 2020-2022. Meanwhile, the size of the board of directors, independence of the board of directors, size of the audit committee, independence of the audit committee and financial knowledge of the audit committee have no effect on financial distress in industrial sector companies listed on the Indonesian Stock Exchange 2020-2022.